HPB P68 Multimetric MRI detects improved quality of the future liver remnant post-dual vein embolization – a novel finding. (7th December 2022) - Sundaravadanan, Senthil; Welsh, Fenella; Sethi, Pulkit; Cresswell, Ben; Connell, John; Knapp, Sina; Nunez, Luis; Kelly, Matt; Brady, Michael; Banerjee, Rajarshi; Rees, Myrddin
Abstract: Background: Optimisation of the future liver remnant (FLR) is crucial to the safety of extended liver resections. This study aimed to assess volume and quality of the FLR pre- and post-dual vein embolisation (DVE) by MRI, in patients with insufficient FLR, needing major hepatectomy. Methods: Of 81 patients recruited in a clinical trial (Precision1:NCT04597710), seven consecutive patients with colorectal liver metastases underwent multiparametric MRI (Hepatica®) pre- and post-DVE (right hepatic and portal vein). One patient had DVE after a first-stage hepatectomy. FLR volume, fibro-inflammation map (corrected T1) and fat (proton density fat fraction, PDFF) was determined. Results: All 7 patients underwent uncomplicated DVE, with significant increase in median(range) %FLR volume at liver surgery [45.7(27.0–57.8)% versus 32.4 (19.5–37.7)%, p=0.016], 46 days (range 28–77) post-DVE. Median(range) FLR cT1 scores reduced post-DVE [747.33 (684–884)ms, versus 771.25(726–945)ms, p=0.047; healthy range<794ms], as did median(range) PDFF scores [3.4 (2–13.25)% versus 6 (1.5–22.5)%, p=0.078; healthy range <5.6%]. No patient developed post-hepatectomy liver failure (PHLF). Conclusions: This novel, non-invasive and readily accessible MRI technique shows that volume and quality of the FLR improves after DVE. This is a significant step in improving surgical decision making in patients with borderline FLR, preventing PHLF and improving outcomes.